Bioreceptivity of Portland and calcium Sulphoaluminate cements in urban sewerage networks. (26th July 2021) - Sawadogo, Awa Yasmina Faridha; Roux, Sébastien; Lecomte, André
Highlights: In sewer, cement paste biocolonisation is managed by environmental conditions. Seasonal weather conditions govern biofilm development on cement pastes surface. BSO colonisation leads mainly to gypsum and ettringite formation. Colonisation rate and the amount of products formed are correlated. Abstract: This paper discusses the comparative biolcolonization of cementitious pastes made with two Portland Cements and two Calcium Sulphoaluminate Cements exposed for 18 months in an actual urban sewerage network at five different sites. After an incubation period of about 18 months all the cement pastes were found to be colonized by suphooxidizing bacteria in the 5 environments studied. The results obtained show that the cementitious nature is not a determining factor and that the conditions of the moment actually favour the accumulation of secondary phases on the surface due to the presence of sulphur that appears because of bacterial activity.